Association of Systemic Inflammatory Response Index and Pan-Immune-Inflammation-Value with Long-Term Adverse Cardiovascular Events in ST-Segment Elevation Myocardial Infarction Patients After Primary Percutaneous Coronary Intervention - Liu Y; Liu J; Liu L; Cao S; Jin T; Chen L; Wu G; Zong G (Dove Medical Press, 2023)
Yehong Liu,1,* Jie Liu,1,* Longqun Liu,2,* Shaoqing Cao,1,3 Tianhui Jin,1 Liang Chen,1,3 Gangyong Wu,1,3 Gangjun Zong1,3 1Department of Cardiology, The 904th Hospital of Joint Logistic Support Force of PLA, Wuxi, Jiangsu, People's Republic of China; 2Department of Respirology, The 904th Hospital of Joint Logistic Support Force of PLA, Wuxi, Jiangsu, People's Republic of China; 3Department of Cardiology, Wuxi Clinical College of Anhui Medical University, Wuxi, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Gangyong Wu; Gangjun Zong, Email wuwangyi520@sina.com; zonggj@163.comAim: Reducing the high morbidity and mortality of ST-segment elevation myocardial infarction (STEMI) and improving patient prognosis remains a major global challenge. This study aimed to explore whether dynamic fluctuations in biomarkers are valuable predictors of prognosis in patients with STEMI.Methods: This study included 216 patients with STEMI. Blood routine tests were performed on admission, 12 h after percutaneous coronary intervention (PCI), and at discharge. Systemic immune-inflammation index (SII), systemic inflammatory response index (SIRI), and pan-immune-inflammation-value (PIV) serum immune-inflammatory markers were calculated. The Cox proportional hazard model was used to assess the factors independently associated with the prognosis of STEMI. The optimal cutoff values for the inflammatory markers were calculated.Results: Eighty-five (39.35%) of the 216 patients had major adverse cardiovascular events (MACEs) during the 1-year follow-up. Most were male (81.18%) with a median age of 64 years (interquartile, 55- 69.5). Killip class ≥ II on admission (hazard ratio [HR], 1.859; 95% CI, 1.169- 2.957; P = 0.009), total stent length (HR, 1.016; 95% CI, 1.003- 1.029; P = 0.019), values of SIRI at 12 h after PCI (HR, 1.079; 95% CI, 1.050- 1.108; P < 0.001), and the Gensini score (HR, 1.014; 95% CI, 1.007- 1.022; P < 0.001) were independently associated with an increased risk of MACEs. Compared with SII, SIRI and PIV calculated at various time points and dynamically fluctuating changes, SIRI (cutoff value, 4.15; 95% CI, 0.701- 0.819; P < 0.001) and PIV (cutoff value, 622.71; 95% CI, 0.674- 0.796; P < 0.001) at 12 h after PCI showed the best efficacy for the prognosis of STEMI.Conclusion: Our study provides relevant evidence to the notion that SIRI or PIV at 12 h after PCI may be more accurate and economical predictors of long-term adverse prognosis in patients with STEMI.Keywords: systemic inflammatory response index, pan-immune-inflammation-value, ST-segment elevation myocardial infarction, major adverse cardiovascular events, prognosis, percutaneous coronary intervention